Creation Of Fake Authentic Deeds By A Notary Which Harms Others - Malinda, Rizka Saraswati; Sunardi, Sunardi (Universitas Islam Malang, 2025)
Abstract : Bad faith includes acts of fraud, a series of misleading others, as well as behavior that ignores legal obligations in order to gain profit. Not a few notaries experience problems in connection with deeds they have made which are declared to be private deeds or become null and void by a court decision as a result of legal defects found in their making. What are the Responsibilities of Notaries for the Contents of Authentic Deeds Made Based on Fake Documents, What are the Legal Consequences of Notarial Deeds Based on Fake Documents. As is known, a person can only be sentenced to a crime if his or her actions meet all the elements of a criminal act formulated in the Articles of the Criminal Law, which is a normative requirement that must be fulfilled if a person can be punished for committing a criminal act, that is, the act must be proven to match all the elements of a criminal act. Sanctions are a coercive tool, apart from punishment, also for complying with provisions stipulated in regulations or agreements. Sanctions are also interpreted as a coercive tool as punishment for disobeying an agreement. A notary can be involved in a criminal case and he can even be held criminally liable if he violates what according to law includes prohibited elements. When it comes to notaries who are asked to be held responsible, a question arises, namely in what way a notary who makes a deed based on false information will be asked to be held criminally responsible if he makes a deed based on false information. The case that occurred in 2023 was that a Notary practicing in the city of Bekasi was legally and convincingly proven guilty of committing the crime of